Impact of haplotypes of TNF in the natural course of infective endocarditis. (25th October 2013) - Giannitsioti, E.; Damoraki, G.; Rokkas, C.; Tsaganos, T.; Fragou, A.; Kannelaki, S.; Athanasia, S.; Giamarellos‐Bourboulis, E. J.; Grobusch, M.
Abstract Based on previous findings for the role of single nucleotide polymorphisms (SNPs) of TNF for the predisposition for bloodstream infections, this study investigates the role of these SNPs at the promoter positions −376, −308, −238 in infective endocarditis (IE). In a case–control study, 83 patients with IE and 83 controls were enrolled. Blood genotyping for the presence of G or A alleles of the three SNPs was carried out using restriction fragment length polymorphisms. Haplotypes were calculated. Patients were mostly infected by Staphylococcus aureus (32.5%) and by species of enterococci (14.3%) and streptococci (14.3%). Carriage of the minor frequency A alleles at −238 of the promoter region of TNF was greater than in controls (8.4% versus 1.2%, p 0.003). The presence of any of the three GGA/GAA/AGA haplotypes was more frequent in patients with IE (OR 8.22, 95CI% 1.8–37.4, p 0.001). After multivariate logistic regression analysis, it was found that the only factor related to fatal outcome was carriage of the wild‐type GGG haplotype (OR, 3.29, 95CI%, 1.05–10.29, p 0.04). GGA, AGA and GAA haplotypes were more frequent in patients with IE than in controls, suggesting a predisposition for IE and a potential protective role against fatal outcome, as the wild‐type GGG haplotype was independently related with death.